ALTERNATE PRICING STRATEGIES IN CONSTRUCTION - Krishna Mochtar; David Arditi (Institute of Research and Community Outreach - Petra Christian University, 2000)
Recent research findings on pricing strategies both in general and in construction are reviewed and explored. First%2C pricing strategy in general%2C mostly in the manufacturing industry%2C is reviewed. It includes the concepts of pricing strategy%2C predatory pricing%2C price wars%2C and price policy development. Second%2C pricing strategy in construction is explored. It includes various pricing models for bid price determination%2C such as the Friedman-Gates models%2C expected utility models%2C risk-pricing model%2C and the crew-day%2C multiple regression%2C and fuzzy-set pricing models. In conclusion%2C pricing strategies in construction are still predominantly based on a cost-based approach. More recent models try to close the gap between the models and the real life conditions of a bidder%5C%27s decision-making process. It appears that there are more problems in cost-based pricing as opposed to market-based pricing. Consequently%2C it is highly recommended that%2C alternative pricing approach such as that are closer to the proposed market-based pricing model need to be explored and developed for use in the construction industry. Abstract in Bahasa Indonesia : Pricing+strategy%2C+cost-based+pricing%2C+market-based+pricing.